Quantitative EEG in children with learning disabilities: analysis of band power Eletrencefalograma quantitativo em crianças com dificuldades de aprendizagem: análise de freqüências - Lineu C. Fonseca; Glória M.A.S. Tedrus; Marcelo G. Chiodi; Jaciara Näf Cerqueira; Josiane M.F. Tonelotto (Arquivos de Neuro-Psiquiatria)
In order to better understand the mechanisms of learning disabilities it is important to evaluate the electroencephalogram parameters and their relation to the results of the Wechsler Intelligence Scale. Thirty-six children with complaints of learning disability were studied. Electroencephalograms were carried out while awake and resting, and the values for absolute and relative powers calculated. The results were compared with those of 36 healthy children paired with respect to age, gender and maternal scholastic level. In the group with learning disabilities, the absolute (in the delta, theta and alpha 1 bands) and relative (theta) power values were higher and the relative power alpha 2 value significantly lower at the majority of the electrodes in relation to the control group. There was a high positive correlation in the children with learning disabilities between the relative power alpha 2 and the verbal, performance and total IQ values. These quantitative electroencephalogram findings in children with learning disabilities have a clear relation with psychological measurements and could be due to brain immaturity. Para compreender melhor os mecanismos das dificuldades de aprendizagem é importante avaliar a relação entre parâmetros do eletrencefalograma e resultados da Escala Weschler de Inteligência. Foram estudadas 36 crianças com queixas de dificuldades de aprendizagem. Foi realizado o eletrencefalograma durante vigília, em repouso e calculados os valores de potência absoluta e relativa. Os resultados foram comparados aos de 36 crianças sadias pareadas quanto a idade, gênero e escolaridade materna. As potências absoluta (das faixas delta, teta e alfa 1) e relativa (teta) foram maiores e a potência relativa alfa 2 foi significativamente menor, na maioria dos eletrodos, no grupo com dificuldade de aprendizagem em relação ao grupo controle. Nas crianças com dificuldade de aprendizagem houve correlação elevada e positiva entre a potência relativa alfa 2 e o QI. Os achados do eletrencefalograma quantitativo das crianças com dificuldade aprendizagem têm nítida relação com medidas psicológicas e podem ser decorrentes de imaturidade cerebral.